2018
DOI: 10.1089/adt.2018.853
|View full text |Cite
|
Sign up to set email alerts
|

Rational Druggability Investigation Toward Selection of Lead Molecules: Impact of the Commonly Used Spices on Inflammatory Diseases

Abstract: Herbal remedies and phytochemicals have been used in traditional medicine. Most of the herbs used in human diet have some major effective elements that can affect various pathways in the human body and play a therapeutic role in healing disorders or diseases. Among the inflammatory diseases, worldwide common disorders possess well-known pathways that can be controlled by diet and behavior. There are some well-established targets that are used for anti-inflammatory drugs like cyclooxygenase type 1 and 2 (COX-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In this study, piperine, an exogenous active alkaloid with no endogenous origin reported so far, was highlighted as potential predictor of breast cancer risk (inverse association), with high stability across penalized models (selection frequencies >90% on the 1,000 bootstraps). Piperine is contained in black and long pepper (33) and is used as feed additive in animal feed, in particular for poultry (34). The human exposure to piperine via this latter source has been estimated at 0.93 mg/metabolic body weight per day (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, piperine, an exogenous active alkaloid with no endogenous origin reported so far, was highlighted as potential predictor of breast cancer risk (inverse association), with high stability across penalized models (selection frequencies >90% on the 1,000 bootstraps). Piperine is contained in black and long pepper (33) and is used as feed additive in animal feed, in particular for poultry (34). The human exposure to piperine via this latter source has been estimated at 0.93 mg/metabolic body weight per day (34).…”
Section: Discussionmentioning
confidence: 99%
“…Several animal or cellular studies suggested a promising spectrum of properties for piperine such as anti-oxidant (35,36), anti-inflammatory (33,35,36), immunomodulatory, bioavailability and absorption promoter for many active molecules (33,37), antiasthmatic, anticonvulsing, antimutagenic, antimycobacterial, and anticancer activities (ref. 33; chemopreventive properties, including inhibition of angiogenesis and increased cell apoptosis), especially in breast cancer models (38)(39)(40). In our study, piperine was in particular positively associated with alcohol intake and with a "Western" dietary pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the complex structures were recaptured from the virtual screening result and the same method was iterated. An excel sheet was xed to investigate all the a nities, hydrogen interaction, steric energy and high re-rank score to recognize the best inhibitor [104][105][106][107][108][109][110][111][112].…”
Section: Drug-drug Comparative Studymentioning
confidence: 99%
“…Inflammatory disorders are caused by enzymes such as cyclooxygenase types 1 and 2 (COX-1 and COX-2), lipooxygenase, prostaglandin receptor (DP 1 ) and prostaglandin D2 receptor (2CRTH2). Zakerali et al (47) selected different spices commonly used in the food industry to observe their ability to inhibit the enzymes that cause inflammatory processes. PIP demonstrated an inhibitory effect of COX-2 and a better affinity value (-7.8 kcal mol -1 ) and energy binding (-85.08 kcal mol -1 ) than aspirin and celecoxib.…”
Section: Antiinflammatory Propertiesmentioning
confidence: 99%